Single-centre retrospective observational study comparing trough blood concentration and safety of teicoplanin formulations. Issue 7 (July 2019) - Shinoda, Rie; Shinoda, Yasutaka; Ohashi, Kengo; Matsuoka, Tomoko; Hirose, Tatsuya; Sugiyama, Tadashi; Yoshimura, Tomoaki
Abstract: Teicoplanin formulations are marketed as antibiotic mixtures with several compounds that share the same core structure. Recent studies conducted in vitro have reported differences in the composition ratio of different teicoplanin products. In this retrospective study, we examined the trough blood concentration of the originator brand and a generic teicoplanin product. Target patients were retrospectively assigned to the originator (Targocid) or generic group. The groups were matched 1:1 using propensity scores. The initial trough blood concentration analysis identified 44 matches. In both groups, the median dosing day for the first measurements was 4, respectively. The initial trough blood concentration of the originator group was significantly higher (mean ± SD, 16.3 ± 4.5 mg/L) than that of the generic group (12.8 ± 4.7 mg/L; 95% CI, −5.4 to −1.6). A significant difference was observed in the frequency of serum creatinine elevation in the study of the frequency of adverse events using Common Terminology Criteria for Adverse Events (originator group, 41.9% vs generic group, 20.9%). In cases where discontinuation was necessary due to side effects, there were three patients in the originator group and one patient in the generic group. This study found that trough blood concentration differed between formulations. Therefore, correction might be necessary while monitoring drug concentration in the blood. Trough blood concentrations are used as surrogate markers for efficacy and safety, so further studies on differences in efficacy and safety between formulations are required.